Determination of Perception and Adaptive Capacity towards Climate Change among Paddy Farmers in State of Kelantan, Malaysia - Anis Nik Abdullah, Nik; Zahidah Abdul Karim, Zalina; Aida Sheikh Hussin, Siti; Shaliza Mohd Khairi, Siti (International Journal of Engineering and Technology, 2018)
Rapid changes in the climatic factors affect paddy farming in Malaysia. As Kelantan is the most vulnerable state to climate variations, its paddy production is negatively affected. Proper mitigation and adaptation approach can reduce paddy farmers’ vulnerability to climate change. Hence, it is important to the paddy farmers to cope with climate change by having the right perception to ensure farmers take the right decisions on dealing with climate change. There are four objectives of this study which include estimating the trend of climate change in Kelantan using Mann-Kendall test, determining paddy farmers’ perceptions towards climate change, measuring paddy farmers’ adaptive capability using Analytic Hierarchy Process (AHP) and ascertaining associated factors of the adaptive capacity of paddy farmers using Binary Logistic Regression. Results showed that majority (85.9%) of paddy farmers in Kelantan perceived changes in climate but only 62.9% of paddy farmers were highly adaptive towards climate change. Finally, age, monthly income, and district were found to be significantly associated with paddy farmers’ adaptive capacity towards climate change. Although, most paddy farmers in Kelantan were highly adaptive towards climate change, government and related agencies still need to take some efforts and initiatives to enhance the farmers’ adaptation towards climate change.